Utilizing polygon segmentation technique to extract and optimize light stripe centerline in line-structured laser 3D scanner. (July 2016) - Qingguo, Tian; Xiangyu, Zhang; Qian, Ma; Baozhen, Ge
Abstract: Light stripe centerline extraction is the basic and key procedure in line-structured laser three-dimensional (3D) scanner. Based on the fact that light stripe׳s contour is approximately parallel to its centerline, a novel contour polygon segmentation method is proposed for extracting and optimizing centerline. Different light stripe segments are identified in images by contour tracking, and then each of them is segmented into several parts using contour polygonization. Interior angle is defined to trim open light stripe polygon and contour to make sure that centerlines extracted from open light stripes do not include superfluous points. Taking advantage of polygon segmentation, piecewise polynomial fitting method and self-adaptive interpolating strategy are adopted to acquire smoother and evenly spaced centerline points. Simulated experiments show that the proposed method can calculate centerlines from images robustly with a 0.309 pixel average accuracy. Point clouds and surface models of different objects acquired by a line-structured laser scanner demonstrate that the proposed method can produce more complete and smoother 3D models compared to other classical methods. Processing time for the proposed method is approximately positive proportional to the number of pixels in image. Quantitative analysis of time used for each sub-procedure puts forward an improvement direction for the proposed method. Highlights: Based on that light stripe׳s contour is approximately parallel to its centerline. Segment light stripe into parts by contour polygon representation. Interior included angle is defined to trim open light stripe׳s polygon and contour. Piecewise polynomial fitting and self-adaptive interpolating strategy are adopted to generate optimized centerline points. Extensive experiments validate the method׳s performance including accuracy, robustness and speed.